2019
DOI: 10.21608/zjar.2019.33404
|View full text |Cite
|
Sign up to set email alerts
|

Recent Techniques for Amelioration the Effect of Heat Stress Conditions on Male Rabbits

Abstract: The present work was conducted to study the effect of selenium (Se) plus vitamin E (Vitam E) and AD 3 E vitamins (Vitam AD 3 E) mixture as two alleviation techniques on heat stressed rabbits during hot summer season of Egypt. In total 45 New Zealand white (NZW) male rabbits were used in this research. The animals were divided into three equal groups. The 1 st group was kept without any treatment and served as control group. The 2 nd and 3 rd groups were supplemented daily 1m/l in drinking water with Se plus E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…However, semen pH did not significantly change due to different supplemental antioxidants. The present findings are in agreement with many studies (Sharaf et al, 2019;El-Kholy et al, 2020;El-Ratel et al, 2021). They reported an alteration in the sperm motility of rabbits' semen associated with high ambient temperature.…”
Section: Semen Qualitysupporting
confidence: 94%
“…However, semen pH did not significantly change due to different supplemental antioxidants. The present findings are in agreement with many studies (Sharaf et al, 2019;El-Kholy et al, 2020;El-Ratel et al, 2021). They reported an alteration in the sperm motility of rabbits' semen associated with high ambient temperature.…”
Section: Semen Qualitysupporting
confidence: 94%
“…Vitamin E can alleviate the immunosuppression caused by the release of adrenal cortex hormone at high temperatures and promote the synthesis of immunoglobulin to improve the body's disease resistance and reduce mortality ( 125 ), vitamin E can also reduce the serum cortisol levels, thereby reducing rabbit's adverse reactions to heat stress ( 126 ). Studies showed that adding vitamin E to the water increased the normal sperm, volume, count, motility, live sperm and T3, T4 hormonal levels, then decreased the rectal, skin, ear temperature and respiration rate, thus improving the fecundity of male rabbits ( 81 ). However, vitamin E supplementation had no significant effect on reducing the body temperature of rabbits under heat stress ( 24 ).…”
Section: Potential Mitigation Strategies Of Nutritional Interventionmentioning
confidence: 99%
“…Furthermore, adding vitamin E to drinking water decreased the serum cortisol concentration, ameliorating HS' unfavorable influences on female rabbits' productivity [98]. Regarding rabbit males, Sharaf et al [99] pointed out that the administration of vitamin E in drinking water enhanced the semen quality characteristics (live sperm, normal sperm, volume, count, and motility) and decreased dead sperm, rectal temperature, skin temperature, ear temperature, and respiration rate under HS conditions, and these findings might be attributed to the antioxidative properties of vitamin E.…”
Section: Vitamin Ementioning
confidence: 99%